MENGUKUR KINERJA SUMBER DAYA MANUSIA DENGAN PENDEKATAN HUMAN RESOURCES SCORECARD - Amalia, Alia Rezki; Haliah Haliah; Nirwana Nirwana (AKUNTANSI 45, 2022)
Human resources are one of the main factors in determining the success of a company, agency, or organization so that it becomes an inseparable unit. Therefore, it is necessary to have human resources with high competence to support the improvement of employee performance. Human resources scorecard is the capacity to design and implement a HR strategic measurement system that represents an important tool that companies used to develop and deploy more effective HR strategies. The purpose of this study is to describe the measurement of employee performance using the Human Resources Scorecard measurement system approach from various perspectives. This study uses a systematic literature review. The results of the review show that the average performance achievement that meets the performance level is good, although there are still some from the perspective of this Human Resources Scorecard that has not been achieved in both the service and manufacturing industries. Consequently, every company must be able to assess the performance of its employees so that it can increase motivation, provide comfort and improve the contribution of each individual in the company so the goals could be achieved.